Management of Thrombotic Thrombocytopenic Purpura with Autoantibodies to ADAMTS-13 and Concurrent Preeclampsia in Pregnancy: Multidisciplinary Team Approach - Patrick, Tiffany; Carlan, Steve J.; Najera, Jose Eugenio; Eastwood, Julie (American Journal of Perinatology Reports, 2012)
Background Thrombotic thrombocytopenic purpura (TTP) can present with many laboratory features of preeclampsia, which can make an accurate diagnosis difficult in late pregnancy. Because the treatments of TTP and preeclampsia are different and the clinical sequelae of delayed therapy potentially lethal, a rapid and accurate diagnosis is important. Case Report We present a case of an acute episode of TTP secondary to acquired autoantibodies complicated by severe preeclampsia with headache and treated with corticosteroids, plasma exchange therapy, magnesium sulfate, and delivery. The postpartum course was complicated and resulted in a prolonged hospital stay. A multidisciplinary team was recruited as consultants. Conclusion Concurrent TTP and severe preeclampsia can result in life-threatening complications. To ensure the best possible clinical outcome, an awareness of the medical systems' resources is required.
Keywords: TTP; severe preeclampsia; multidisciplinary team; autoantibodies